Predicting bank failures : a comparison of the Cox proportional hazards model and time-varying covariates model. - Cheng, Philip Yim Kwong. (2008)
As a contribution to bank regulation by improving the accuracy of predicting failed banks, I first illustrate the use of martingale and other residuals as diagnostic checks for Cox’s proportional hazards model. Second, I discuss and substantiate the claim that a time-varying covariates model is superior to the Cox model as a bank failure model.